2021
DOI: 10.2147/jpr.s332224
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Analysis Reveals Abnormal Static and Dynamic Low-Frequency Oscillations Indicative of Long-Term Menstrual Pain in Primary Dysmenorrhea Patients

Abstract: Background: Previous neuroimaging studies demonstrated that patients with primary dysmenorrhea (PD) exhibited dysfunctional resting-state brain activity. However, alterations of dynamic brain activity in PD patients have not been fully characterized. Purpose: Our study aimed to assess the effect of long-term menstrual pain on changes in static and dynamic neural activity in PD patients. Material and Methods: Twenty-eight PD patients and 28 healthy controls (HCs) underwent resting-state magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Compared with other machine learning methods, such as random forest, naïve Bayes, and convolutional neural network. SVM methods have been successfully used to classify diseases, such as iridocyclitis ( Tong et al, 2021 ), primary dysmenorrhea ( Gui et al, 2021 ), and major depressive disorder ( Gao et al, 2021 ). However, no studies have used SVM and VMHC methods to distinguish patients with CE from HCs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other machine learning methods, such as random forest, naïve Bayes, and convolutional neural network. SVM methods have been successfully used to classify diseases, such as iridocyclitis ( Tong et al, 2021 ), primary dysmenorrhea ( Gui et al, 2021 ), and major depressive disorder ( Gao et al, 2021 ). However, no studies have used SVM and VMHC methods to distinguish patients with CE from HCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the application of artificial intelligence in the medical field is still in the initial stage, with more in-depth development of machine learning technology, it will become a general trend for doctors to use artificial intelligence to diagnose and manage the health of the patients in the future. SVM has been widely applied in various diseases and achieved great classification performance ( Chan et al, 2019 ; Gui et al, 2021 ). Using the SVM classifier, the patients with TIA could be differentiated from HCs by dynamic local metrics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cerebellum activation may also be related to the transmission of negative emotional states caused by pain and mental stress ( Wittbrodt et al, 2020 ). RS-fMRI studies have shown abnormal local brain activity in the cerebellum and increased FC between the cerebellum and hippocampus in patients with chronic pain, which are closely related to pain perception and emotion regulation ( Wang et al, 2015 , 2016 ; Wei et al, 2020 ; Gui et al, 2021 ). In this study, TMD patients showed decreased ALFF of the right cerebellum_crus2 and increased FC between the PHG and vermis, and associated with the degree of oral-facial pain and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%